Mucopolysaccharidosis: A rare case from ophthalmology perspective - Santosh Singh Patel; Rajesh Kumar Sahu; Reshu Malhotra; Anju Bhaskar; A. K. Chandrakar (Journal of Clinical Ophthalmology and Research)
The purpose of this article was to report a rare case of mucopolysaccharidosis (MPS) type-I, Hurler–Scheie affecting a 10-year-old boy with a combination of ophthalmological, skeletal, neurological, orodental, and radiological findings. MPSs are a group of lysosomal storage disorders caused by inborn errors of glycosaminoglycan metabolism. MPS type-I is a rare autosomal recessive disorder that is clinically progressive caused by deficiency of the lysosomal enzyme, α-L-iduronidase, which is required to break down heparan and dermatan sulfates resulting in progressive accumulation of glycosaminoglycans within the lysosomes, subsequently leading to multiorgan dysfunction and damage. Newer treatment modalities such as hematopoietic stem cell transplantation and enzyme-replacement therapy have increased the life span of many MPS patients and created the need to improve the management of ocular symptoms.